Kepastian Hukum Dalam Kekayaan Intelektual: Perlindungan Desain Industri Melalui Unsur Kebaruan di Indonesia - Alfariz Maulana Reza (Nagari Law Review, 2021)
Protection of industrial designs is very important and becomes a priority for national economic development so that Indonesia's strategies and policies in ensuring and providing protection for industrial designs can run effectively, it will be in line with the increasing ability and competitiveness of industrial design creators in national and international free markets. This is in line with the considerations in the Industrial Design Law, which states that in order to advance an industry that is able to compete in the scope of national and international trade, it is necessary to create a climate that encourages innovation. The absence of a clear definition related to novelty in industrial design creates ambiguity and uncertainty for people to innovate, in this paper the approaches used are the statutory approach, the case approach, and the comparative approach. Then legal certainty refers to the application of a clear, permanent, consistent and consequent law whose implementation cannot be influenced by subjective conditions, therefore in order to achieve legal certainty in ensuring that industrial design registration is carried out objectively, the element of novelty is the first registration system. must be supplemented by other elements such as the individual character of the European industrial design protection system.